PENGARUH SUDUT KAWAT ANYAMAN BAJA TAHAN KARAT 304 DAN PENAMBAHAN MG TERHADAP SIFAT TARIK DAN STRUKTUR MIKRO KOMPOSIT AL-MG/ANYAMAN KAWAT SS 304 - Muhammad Hilman (Jurusan Teknik Mesin, 2022)
In recent years, industrial development in the material sector has increased rapidly along with advanced human resources. The development of the material industry has created a need for materials that have good quality and are efficient. One of them is about composite materials that have been widely developed. Composite is a material made of two elements, including a matrix and a booster. SS 304 stainless steel wire is one of the booster materials used in the manufacture of aluminum composites because of its low cost, increased wettability and good tensile strength. Magnesium is also useful for increasing wettability and good mechanical strength in aluminum alloys. In this study, the Al-Mg/SS 304 composite with the stirring method was used to determine the effect of the angle of the SS 304 stainless steel wire mesh and the addition of Mg on the tensile properties and microstructure of the Al-Mg/SS 304 woven wire composite. Tensile strength tests were carried out. and microstructure. Value results. The highest tensile strength value was at the webbing angle (0o) with 181.15 MPa. The results of the observation of the microstructure, there are still cavities that occur, but will decrease with the addition of magnesium as much as 4%.